PERAN GURU PADA TRANSFORMASI PENDIDIKAN DALAM MENYONGSONG GENERASI EMAS 2045 - Savira, Liza (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
This research investigates the pivotal role of teachers in the transformative journey of education, aiming to shape the Golden Generation of 2045. The study focuses on the qualitative methodology to delve into the multifaceted aspects of this transformative process. The primary objective is to explore how teachers contribute to reshaping the educational landscape to meet the evolving needs of future generations. This research adopts a descriptive qualitative approach as a strategy to unveil new meanings, elucidate a particular condition, determine the frequency of occurrences, and categorize information. In processing the data, the researcher systematically analyzes and presents facts, facilitating understanding and drawing conclusions. The data collection method employed is a literature review, wherein the researcher accesses diverse information sources through online libraries, including books, journals, and other relevant references. Our findings highlight that teachers play a central role in not only imparting knowledge but also fostering critical thinking, creativity, and adaptability among students. The study reveals that innovative teaching methods, professional development initiatives, and a supportive educational ecosystem are crucial in preparing students for the challenges and opportunities of the future. As we anticipate the Golden Generation of 2045, this research underscores the importance of continuous collaboration between educators, policymakers, and stakeholders to create an environment that nurtures the holistic development of students. The insights from this study contribute to the ongoing discourse on educational transformation and serve as a guide for shaping pedagogical practices aligned with the aspirations of the next generation.